Die Evolution des Strafrechts Strafverfassungsrechtliche, europastrafrechtliche und kriminalpolitische Wirkungen auf Strafgesetzgebung - Brodowski, Dominik (Neue Schriften zum Strafrecht, 2023)
The German legislature amends the German Criminal Code approximately six times per year. Such modifications - and the absence of further such modifications - are shaped and limited by constitutional law, by European and international norms, and by criminal policy decisions. In this thesis, the author analyzes the influences by constitutional law, European (criminal) law and criminal policy on the current evolution of German criminal law, and draws conclusions on the (dynamic) level of legal certainty that is required for provisions of substantive criminal law